2013
DOI: 10.1080/03014223.2012.731006
|View full text |Cite
|
Sign up to set email alerts
|

Bat fatalities at two wind farms in Tasmania, Australia: bat characteristics, and spatial and temporal patterns

Abstract: Bat carcasses from two wind farms in Tasmania (2002Á2010) were assessed to determine the species, sex, age, reproductive state, morphometrics, presence of food in the gastrointestinal tract, and evidence of spatial and seasonal patterns. Thirty-eight of the 54 carcasses were Gould's wattled bats, with another 14 likely to be, and two Vespadelus sp. All but two were adults, with an equal ratio of females and males. None were actively breeding when found, and five of the six bats tested, had not been recently f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 28 publications
2
25
1
Order By: Relevance
“…Interestingly, Grodsky (2010) found that bat fatalities were actually lower near the Horicon Marsh in Wisconsin. Hull and Cawthen (2012) found no relationships between bat fatalities and proximity of turbines to the coast or vegetation. Hence, correlating high-risk locations with particular habitat types or topographic patterns has proven difficult and inconsistent.…”
Section: Habitat Relationshipsmentioning
confidence: 77%
See 2 more Smart Citations
“…Interestingly, Grodsky (2010) found that bat fatalities were actually lower near the Horicon Marsh in Wisconsin. Hull and Cawthen (2012) found no relationships between bat fatalities and proximity of turbines to the coast or vegetation. Hence, correlating high-risk locations with particular habitat types or topographic patterns has proven difficult and inconsistent.…”
Section: Habitat Relationshipsmentioning
confidence: 77%
“…Such consistent temporal patterns of fatality are helpful when predicting high-risk periods and applying some mitigation measures such as raising turbine cut-in speed ). Hull and Cawthen (2012) noted that fatalities predominantly occurred in autumn in Tasmania, where the climate is temperate. However, in the tropical Isthmus of Tehuantepec in Mexico, while 46 % of bat fatalities were found in the summer rainy season, no clear pattern in bat deaths associated with any season emerged.…”
Section: Temporal Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fi rst reports of bat fatalities at wind farms occurred in North America and Europe during the 1990s (Kunz et al 2007 ;Rydell et al 2010 ). However, the occurrence of bat fatalities at wind farms is a global phenomenon with cases described from numerous countries including Australia (Hull and Cawthen 2013 ) and South Africa (Doty and Martin 2013 ). The lack of information on the impact of wind farms on bat populations refl ects the severity and poor understanding of the problem.…”
Section: Effects Of Solar Plants and Wind Farms On Wildlifementioning
confidence: 99%
“…There are no consistent sex or age biases in bat mortality during these periods (Arnett et al . 2008 ;Rydell et al 2010 ;Hull and Cawthen 2013 ). Young bats are not more vulnerable despite their typical dispersal behavior and expected lack of experience.…”
Section: Effects Of Solar Plants and Wind Farms On Wildlifementioning
confidence: 99%